Academic Counseling for Student-Athletes: A Model - Coleman, Victoria D.; Barker, Shirl A. (My University, 1991)
Counseling for student-athletes is gaining national prominence as new regulations, guidelines, institutional requirements, and public concern focus on academic performance. Big-time athletics has presented colleges and universities with new challenges for educating and graduating student-athletes. While academic counseling is often provided for this population, comprehensive programs that address personal, academic, social, and athletic needs are limited. This article described an academic counseling model for student-athletes that can enhance their academic performance. The model consists of the following components: (1) individual assessment and evaluation; (2) study table; (3) academic support and monitoring; (4) staff development; and (5) information dissemination, research, and evaluation.
Keywords: academic support; models